The electric field distributions in anatomical head models during transcranial direct current stimulation for post‐stroke rehabilitation. Issue 1 (3rd January 2017) - Manoli, Zoi; Parazzini, Marta; Ravazzani, Paolo; Samaras, Theodoros
Abstract : Purpose: The lack of knowledge of the electric field distribution inside the brain of stroke patients receiving transcranial direct current stimulation (tDCS) calls for estimating it computationally. Moreover, the impact on this distribution of a novel clinical management approach which involves secondary motor areas (SMA) in stroke rehabilitation needs to be evaluated. Finally, the differences in the electric field distributions due to gender and age need to be investigated. Methods: This work presents the development of two different anatomical models (young adult female and elderly male) with an ischemic stroke region of spherical volume 10 cm 3 or 50 cm 3, using numerical models of the Virtual Population (ViP). The stroke phase was considered as acute or chronic, resulting in different electrical properties of the area. Two different electrode montages were used — One over the lesion area and the contralateral supra‐orbital region and the other over the SMA and the contralateral supra‐orbital region. A quasi‐electrostatic solver was used to numerically solve the Laplace equation with the finite‐difference technique. Both the 99th percentile of the electric field intensity distribution ("E peak value") and the percentage of the tissue volumes with electric field intensity over 50% and 70% of the E peak value were assessed inside the target areas of the primary motor cortex (M1) and the SMA, as well as in other brain tissues (hypothalamus and cerebellum). Results: In the acute phase of an ischemic stroke, the normalized electric field intensity distributions do not differ noticeably compared to those in the brain of a healthy person (mean square difference < 2%). The difference becomes larger (up to 4.5%) for the chronic phase of a large ischemic lesion. Moreover, the maximum values of the induced electric field in the tissues in the SMA are almost equal for both electrode montages. The peak values of the electric field distribution ("E peak values") in cerebellum and hypothalamus for both electrode montages are rather small but different from those of healthy patients. The largest difference of 21% decrease with respect to a healthy subject was noticed in the elder adult model with a large chronic lesion. The comparison of the different electrode montages shows that the use of a stimulating electrode over the affected area creates larger values of the electric field in M1, by up to 26% for a small chronic lesion in the young female model. On the contrary, the montage does not affect considerably (change less than 8%) the E peak values in the SMA. This implies that for exciting M1, the M1–Fp2 montage should be favored. Conclusions: The presence and the phase of an ischemic stroke lesion, as well as the configuration of electrode montages affect the distribution and the maximum value of the electric field induced in tissues. Moreover, patients whom seem to benefit most from tDCS are those in the chronic phase of an ischemic stroke, since contrasts in the tissue conductivity result in a higher electric field induced around the lesion volume, which could stimulate the remaining healthy tissue in the area.